Pengaruh Self Efficacy terhadap Kemampuan Komunikasi Matematis melalui Pembelajaran dengan Menggunakan Aplikasi SPSS - Ramadhani, Ramadhani; Harahap, Juli Yanti (IAIN PADANGSIDIMPUAN, 2020)
This study aims to determine the effect of self efficacy on students' mathematical communication skills through learning using the SPSS application. The use of SPSS applications in learning, specifically in Education Statistics courses supports for students in subject matter. This research is a correlation approach. All students of Semester VII Mathematics Education at the Universitas Muslim Nusantara Al Washliyah be population in this study. By using a sample of research in Semester VII-A Academic Year 2019/2020. The research instrument consisted of tests of mathematical communication skills and self efficacy questionnaires. Tests and questionnaires were provided after the learning process using the SPSS application. This research analyzed by using regression analysis. The results of this study indicate that the correlation value of 0.660 means that it is a strong ability for students' mathematical communication skills. And the regression equation is Y = 0,62X + 66,571.